On some properties of one Očan type topology - Biadrytski, Aliaksandr S. (Journal of the Belarusian State University. Mathematics and Informatics, 2024)
The relation between one Očan type topology and other hyperspace topologies, such as locally-finite topology, Fell topology, Hausdorff metric topology are studied. In the second part of the article we solve the problem of continuous extension of a map X →f Y on hyperspaces endowed with the Očan topology mentioned above. As a result, it’s proved that closed maps and only them have such extension.